Pengembangan Media Pembelajaran Berbasis Simulator Digital Menggunakan Smart Apps Creator (SAC) pada Mata Pelajaran Penerapan Rangkaian Elektronika (PRE) di SMKN 1 Padang - Shawfani, Aditya (Universitas Negeri Padang, 2024)
This research aims to develop Digital Simulator-based learning media using Smart Apps Creator (SAC) in the Application of Electronic Circuits (PRE) subject at SMKN 1 Padang and to determine the level of validity and practicality of the learning media that has been created. This learning media was developed using the Define, Design, Development, Disseminate (4D Model) research model. This learning media will be tested for validity and practicality testing (user trials). Validity testing was carried out by material experts and media experts. The practicality test was carried out by a small group of twenty students. The validity test results obtained were 0.975 from media expert validators which were categorized as